Challenges in Teaching English Faced by English Teachers at MTsN Taliwang, Indonesia - Aisyah Mumary Songbatumis (Universitas Muhammadiyah Yogyakarta, 2017)
Teaching English as a foreign language is a challenging task, particularly when it is done in places where English serves a very limited purpose. This study attempted to investigate the challenges in teaching English as well as the solutions taken by the English teachers at MTsN Taliwang. The study captured the English teachers’ point of view in facing English teaching challenges in the classroom and the solutions they implemented to solve them through interview. A number of challenges emerged, partly coming from students, partly from teachers, and partly from the school’s facility, namely, students’ lack of vocabulary mastery, students’ low concentration, students’ low motivation, students’ lack of discipline, students’ boredom, speaking problem, shortage of teachers’ training, teachers’ language proficiency issue, limited mastery of teaching methods, teachers’ unfamiliarity to high-tech, teachers’ lack of professional development, inadequate resources and facilities, and time constraint. The solutions to overcome these challenges were also suggested in this study. Reforming attitude, applying various teaching methods and techniques, improving resources and facilities, matching students’ level and learning situation, using and providing dictionary, making use of available resources and facilities, providing motivational feedback, looking for appropriate methods or materials, and teachers’ self-reflection might be quite helpful in coping the English teaching challenges in classroom situation.Keywords: teaching, English language, challenges, solutions